World economic outlook October 1988 : a survey by the staff of the International Monetary Fund - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This survey contains world economic and financial development outlook of various country around the globe.
Some issues have also unique subtitles.
Issues Oct. 2007- will only include Part A of the Statistical Appendix; Part B will be available online only.
asm 21/01/2019
Ref.
Keywords: Economic history; Economic conditions; International economics; Economic development